Protecting Human Rights in The Light of Marine Pollution in Sri Lanka: A Critical Study on The Impact of Shipping-Induced Pollution - Fathima Simrana, F. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and surana International Attorneys India, 2025)
Sri Lanka, strategically positioned along major international maritime trade routes, faces significant environment and human rights challenges due to shipping-induced marine pollution. The growth in shipping activities has raised concerns about the effectiveness of Sri Lanka’s legal framework in mitigating pollution while protecting human rights, particularly those of coastal communities. Despites existing national legislation and international convention gaps persists in explicitly incorporating human rights principles into environmental laws. This research addresses the alignment of Sri Lanka's marine environmental law enforcement mechanisms with human rights principles for effectively mitigating shipping-induced marine pollution. The primary objectives are to assess the implementation and enforcement of existing environmental laws regarding shipping-induced marine pollution, evaluate the impact of this pollution on human rights, and propose recommendations for enhancing legal and policy frameworks. This research employs a qualitative methodology based on secondary data from scholarly articles, verified news sources, legislation, international conventions and case law. The study critically examines the alignment of Sri Lanka’s marine environmental law enforcement mechanisms with human rights principles. The study finds that while existing environmental laws provide a basic frame for pollution prevention and control, they inadequately address the broader human rights implications. Coastal communities continue to suffer from health hazards, economic losses and disruption to their livelihoods due to inadequate enforcement and accountability mechanisms. Moreover, the constitution of Sri Lanka lacks explicit recognition of environmental rights in this issues. Therefore, the research underscores the necessity of explicitly integrating human rights considerations into national environmental legislation. Strengthening enforcement and accountability mechanisms are crucial to effectively address shipping-induced marine pollution and safeguard the rights of affected communities.
Keywords: Marine pollution; Human rights; Environmental law; Sri Lanka; Shipping activities